Increasing Professionalism in Public Finance Management : A Case Study of the United Kingdom - Jane Squire, Sarah; Beazley, Ivor (Washington, DC: World Bank, 2016)
In countries such as the United Kingdom, the need to manage fi nances in a professional manner has been hampered by the severe fi scal constraints of the 2008 fi nancial crisis. These pressures are likely to persist in the long term as a result of an aging population and rising public expectations of the quality of public services.